2020
DOI: 10.3390/cells9122657
|View full text |Cite
|
Sign up to set email alerts
|

The Failed Clinical Story of Myostatin Inhibitors against Duchenne Muscular Dystrophy: Exploring the Biology behind the Battle

Abstract: Myostatin inhibition therapy has held much promise for the treatment of muscle wasting disorders. This is particularly true for the fatal myopathy, Duchenne Muscular Dystrophy (DMD). Following on from promising pre-clinical data in dystrophin-deficient mice and dogs, several clinical trials were initiated in DMD patients using different modality myostatin inhibition therapies. All failed to show modification of disease course as dictated by the primary and secondary outcome measures selected: the myostatin inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 135 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…Another pathway is myostatin inhibition using compounds such as follistatin, ACE-031, domagrozumab, and the GDF11 propeptide that inhibit or antagonize the effect of myostatin [ 52 , 53 , 54 , 55 , 56 , 57 ]. However, the results from animal models and patients with DMD have raised some concerns related to other biological functions of myostatin that affect the metabolism and oxidative capacity of muscle fibers [ 52 , 58 ]. Second, genotyping of patients with DMD for LTBP4 and SPP1 could be considered, especially in the Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway is myostatin inhibition using compounds such as follistatin, ACE-031, domagrozumab, and the GDF11 propeptide that inhibit or antagonize the effect of myostatin [ 52 , 53 , 54 , 55 , 56 , 57 ]. However, the results from animal models and patients with DMD have raised some concerns related to other biological functions of myostatin that affect the metabolism and oxidative capacity of muscle fibers [ 52 , 58 ]. Second, genotyping of patients with DMD for LTBP4 and SPP1 could be considered, especially in the Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…Additional clinical data on patients with muscle atrophy-linked neuromuscular disorders reveal that patients with advanced muscle wasting and atrophy have significant decreases in circulating myostatin levels and myostatin expression in muscle biopsies ( Burch et al, 2017 ; Mariot et al, 2017 ) in contrast to other studies ( Brandt et al, 2012 ). Myostatin antagonists, employed in clinical trials in DMD, for example, may thus be targeting an already down-regulated ligand, resulting in less significant patient outcomes ( Mariot et al, 2017 ; Rybalka et al, 2020 ). A recent 2020 review by Rybalka and colleagues highlights this and other biological and therapeutic reasons for the lack of success with using myostatin inhibitors in human DMD ( Rybalka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin antagonists, employed in clinical trials in DMD, for example, may thus be targeting an already down-regulated ligand, resulting in less significant patient outcomes ( Mariot et al, 2017 ; Rybalka et al, 2020 ). A recent 2020 review by Rybalka and colleagues highlights this and other biological and therapeutic reasons for the lack of success with using myostatin inhibitors in human DMD ( Rybalka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in those very same studies showing elevated activin A, circulating myostatin was found decreased [147,149], similar to myostatin gene expression in gastric cancer patients with minimal or no weight loss [152,153]. Interestingly, circulating myostatin is substantially lower in humans than in mice [154], perhaps contributing to the poor translation of blocking myostatin alone [19]. More studies are needed to fully understand the role of activin A in muscle atrophy, also keeping in mind that low muscle size, as calculated from computed tomography (CT) scans, was not found to correlate with activin A levels [148].…”
Section: Levels Of Acvr2 Ligands In Cancer Cachexia and In Cancer Treatmentmentioning
confidence: 93%